CE: Pain and Mental Health Symptoms After Traumatic Orthopedic Injury. Issue 9 (September 2022) - Breazeale, Stephen; Barrett, Stephanie; Holland, William; Webb, Megan
ABSTRACT: This article highlights the need to screen survivors of traumatic orthopedic injuries for postinjury symptoms associated with stressor-related disorders such as acute stress disorder and posttraumatic stress disorder, including pain, sleep disturbances, anxiety, and depression. The authors discuss the presentation of these postinjury symptoms, the instruments used to screen for each, the various pharmacological and nonpharmacological treatments, and the nursing implications for managing postinjury symptoms in traumatic orthopedic injury survivors. Abstract : A review of the presentation, screening, and treatment of postinjury symptoms associated with stressor-related disorders such as acute stress disorder and posttraumatic stress disorder, including pain, sleep disturbances, anxiety, and depression.